Analisis Hubungan Melodi Dendang dan Sarunai pada Arak-arakan Babako di Kuranji - Rayhan Kurnia; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2024)
This study aims to find the relationship between dendang and sarunai in the procession of babako in Kuranji. The purpose of this study is to find the relationship between dendang and sarunai in the procession of babako in Kuranji. The benefits obtained in this study is to add insight to the researchers themselves, in addition to the results of this study can be used as material for appreciation of folk music in the educational environment or society. And as a source of information and documentation in the field of government about the change and sustainability of local culture, and for the motivation of Tourism Development in the field of traditional arts that can be performed for tourists.The results of the study relationship between dendang and sarunai very tied to the performance of talempong pacik. In the song / Dendang Racun Dunia, Baburu Babi and Singgalang apparently dendang only follow the form of the show that exists in sarunai and rhythmic patterns that exist in the form of performance tasa, tambua, talempong. Dendang and sarunai only contribute to the content of the performance dendang and sarunai not dendang and sarunai apart from the tempo in the rhythm show but still tied and dendang do not have to follow the performance in tasa, tambua, talempong.